More Than a Carpenter - McDowell, Josh (Minneapolis, Minnesota Living Books, 1982)
Josh McDowell thought Christians must be "out of their minds." He put them down. He argued against their faith. But eventually he saw that his arguments wouldn't stand up. Jesus Christ really was God in human flesh. Josh became a speaker on college and
Keywords: Jesus Christ -- Person and offices. Jesus Christ. Christology